Assessment of Aflatoxin Biocontrol Strategies Implemented by Private Sector Entities for Managing Aflatoxin Contamination in Nigerian Agricultural Systems - Ola, O. T.; Ogedengbe, O. O.; Raji, T. M.; Eze, B.; Chama, M.; Ilori, O. N.; Awofisayo, M. A.; Kaptoge, L.; Bandyopadhyay, R.; Ortega-Beltran, A.; Ndarubu, A. A. (Research Perspectives of Microbiology and Biotechnology Vol. 7, 2024)
Aflatoxins are toxic compounds produced by several Aspergillus species that contaminate various crops. The impact of aflatoxin on the health of humans and livestock is a concern across the globe. Income, trade, and development sectors are affected as well. There are several technologies to prevent aflatoxin contamination but there are difficulties in having farmers use them. Several Aspergillus species can produce aflatoxins, however, A. flavus is the most common causal agent of contamination and therefore of global interest. In Nigeria, an aflatoxin biocontrol product containing atoxigenic isolates of A. flavus has been registered with regulatory authorities and is now being produced at scale by the private company Harvestfield Industries Limited (HIL). The current study reports results of biocontrol effectiveness trials in maize conducted by HIL during 2020 in several locations across Nigeria and compared to untreated maize from nearby locations. Farmers and farmer-field selections were carried out in collaboration with the lead farmers from MAGPAMAN and Agricultural Extension Agents (AEAs) of the Agricultural Development Project (ADP). Biocontrol application was conducted in fields across the six geopolitical regions of Nigeria during the 2020 cropping season, which spans from April to October. Also, maize was collected from open markets to assess levels of contamination. All treated maize met tolerance thresholds (i.e., <4ppb total aflatoxin). In contrast, most maize from untreated fields had a higher risk of aflatoxin contamination, with some areas averaging 38.5 ppb total aflatoxin. Maize from open markets had aflatoxin above tolerance thresholds with even an average of up to 90.3 ppb. For the biocontrol treatment comparisons, means were separated using paired Student t-tests. Results from the trials were presented in a National Workshop attended by key officers of Government agencies, farmer organizations, the private sector, NGOs, and donors. Overall, we report (i) efforts spearheaded by the private sector to have aflatoxin management strategies used at scale in Nigeria, and (ii) deliberations of key stakeholders to ensure the safety of crops produced in Nigeria for the benefit of farmers, consumers, and industries. With improved, refined strategies, aflatoxin management programs will surely result in reduced aflatoxin contamination and exposure in Nigeria and elsewhere.